Pandemic consulting. How private consultants leverage public crisis management. Issue 3 (1st August 2022) - Vogelpohl, Anne; Hurl, Chris; Howard, Michael; Marciano, Reut; Purandare, Uttara; Sturdy, Andrew
ABSTRACT: This forum article discusses how the Covid19-pandemic as a major public crisis is transforming the relationship between governments and management consultants, contributing to the deepening presence of consulting firms in policy-making and governance. It shows how the crisis has entrenched private advice in public policymaking as governments are spending millions of dollars on transnational professional service firms like McKinsey, KPMG, Deloitte and Accenture to coordinate their pandemic responses. Drawing from comparative research of India, Australia, UK, Germany and Canada, we outline how interests have been aligned through both the state's demand for quick advice and the readily available supply of expertise provided by firms seeking to expand their markets. In this context, we note that professional services firms have been able to leverage their scope, scale, speed and networks in deepening their role in governance, moving beyond simply advising governments to providing core administrative functions. We conclude by discussing the implications for democracy and the possibilities for contestation.